Effect of Child Birth Preparation Classes on Empowering Iranian Pregnant Women: A Systematic Review - Masoumeh Rajabi Naeeni; Masoumeh Simbar (Hamadan University of Medical Sciences, 2018)
Background and Objective: Pregnancy is one of the most important stages of women's life, which results in significant physical, mental, and social changes. Therefore, the empowerment of pregnant women to adapt to these changes is necessary. Child birth preparation classes have been targeted toward the fulfillment of this purpose. Regarding this, the present study was conducted to review the studies on the effect of child birth preparation classes on empowering pregnant women in Iran. Materials and Methods: The relevant articles published up to the beginning of April 2017 were searched in 12 valid databases and the Google Scholar search engine using several keywords. The search process resulted in the retrieval of 96 articles, the eligibility of which was investigated by studying their abstracts and full-text versions. Finally, 10 studies were included in the systematic review. Results: The results revealed a statistically significant difference between the intervention and control groups in terms of tiredness, postpartum depression, duration of admission, as well as prenatal daily activities, back pain, and pelvic pain during pregnancy. In addition, there was a significant statistical difference between the two groups regarding the duration of active labor phase and the second stage of labor, anxiety level, self-efficacy, neonatal birth weight, satisfaction rate, and normal vaginal delivery rate. Totally, 81.46% and 55.88% of the women in the intervention and control groups had normal vaginal delivery, respectively. Conclusion: Based on the results of the reviewed studies, it can be concluded that the education presented in child birth preparation classes is effective in the empowerment of pregnant women. Therefore, it is recommended to encourage mothers to actively participate in these educational classes and also develop these classes across the country.